Experimental Determination of Biologically Active Compounds in Pomace of Siberian Beet and Carrot - Anastasia V. Kozhemayko; Irina Yu. Sergeeva; Irina V. Dolgolyuk (Техника и технология пищевых производств)
Introduction. With the development of the food and processing industry, the matter of environmental pollution is becoming more and more acute. Environmental protection is based on the principle of rational use of natural resources and sustainable technology. Vegetable pomace is a secondary raw material; its amount depends on the production technology and equipment. The observed positive trend in the gross harvest of vegetables in open ground can increase the number of vegetable processing enterprises and the capacity of existing enterprises. Eventually, waste will start accumulating at processing sites, and it will have to be used as raw materials. The present paper features the content of biologically active substances in pomace of carrots and beets grown on the territory of the Siberian region and introduces options for their further use in functional foods. Study objects and methods. The research featured carrot pomace of the varieties Losinoostrovskaya, Nantskaya, and Queen of Autumn, as well as beet pomace of varieties Cylinder and Bordeaux. All the samples were harvested in the Kemerovo region in 2019. Determination of physical and chemical parameters was carried out using standard methods. Carotenoids, flavonoids, β-cyanine were studied using spectrometry and photocolorimetric method. Results and discussion. The experiment featured the content of bioactive substances in pomace of carrots and beets obtained during industrial processing. The content of carotenoids in carrots (mg of β-carotene per 100 g of dry weight): for Losinoostrovskaya variety – 23.56 ± 0.23; Nantskaya – 25.32 ± 0.18; Queen of Autumn – 20.78 ± 0.25. Flavonoid content (mg of catechol equivalent per 100 g of dry weight): Losinoostrovskaya – 12.02 ± 0.37; Nantskaya – 13.45 ± 0.56; Queen of Autumn – 11.50 ± 0.48. The content of β-cyanine in beets (mg per 100 g of dry weight): Cylinder – 100.0 ± 8.5; Bordeaux – 35.0 ± 1.8. The nutritional value of carrot and beet pomace with a mass fraction of moisture was 10%. The nutritional value of vegetable pomace is due to the high content of dietary fiber; therefore, the raw materials can be considered for functional food production. The content of biologically active substances in vegetable pomace (flavonoids, carotenoids, β-cyanines) can enhance the functional orientation of this secondary raw material when used in food technologies for the production of food of high nutritional value. Conclusion. The results obtained will make it possible to use the biochemical potential of plant raw materials in many aspects, as well as to obtain new functional food products, thereby expanding the range of healthy foods.